IMPLIKASI YURIDIS UNDANG-UNDANG CIPTA KERJA NOMOR 11 TAHUN 2020 PASAL 88C AYAT 1 DAN 2 TENTANG UPAH MINIMUM KABUPATEN ATAU KOTA TERHADAP DUNIA BISNIS - Fatmala, Dila; Kusuma Dewi, Retno Catur; Wardan, Avindo a Charima (UNES Law Review, 2023)
Along with the national development program carried out by the government, a work copyright law was enacted which is expected to provide ease of doing business, inflow of investment, so as to create jobs and improve people's welfare. This study aims to examine the impact of Article 88C paragraphs 1 and 2 of the work copyright law number 11 of 2020 on district minimum wages in Indonesia. Because there were many controversies, demonstrations by workers and students emerged who understood that this article is more detrimental to workers because it lowers the district or city minimum wage. The research method used is descriptive and normative methods in the form of literature studies. In the perspective of Indonesian law, this article provides protection for workers and companies in order to create economic stability. However, there are still challenges and problems in determining efforts to determine the District/City Minimum Wage, such as if it only follows the Provincial Minimum Wage then the District/City Minimum Wage may be lower and vice versa. Therefore, discussions and in-depth studies are needed to consider the interests of all parties, including workers, employers, and the general public.